Kidney symptom questionnaire: Development, content validation and relationship with quality of life. Issue 3 (24th May 2018) - Brown, Stephanie A.; Tyrer, Freya; Clarke, Amy L.; Lloyd‐Davies, Laetitia H.; Niyi‐Odumosu, Faatihah A.; Nah, Ryan Guo Quan; Stein, Andrew G.; Tarrant, Carolyn; Smith, Alice C.
SUMMARY: Background: Chronic kidney disease (CKD) is associated with a range of symptoms, even at early stages. The importance of patient symptom experience is increasingly recognised, but validated symptom scores are lacking. Objectives: This study aimed to refine an existing symptom questionnaire for use with patients not requiring renal replacement therapy (RRT), carry out content validity testing and explore convergent validity by comparing symptom scores with quality of life (QoL). Design: A mixed‐methods approach involving questionnaires, semi‐structured interviews and a focus group. Participants: Patients with CKD not undergoing RRT and expert health professionals. Approach: Two hundred and nineteen patients completed an existing symptom questionnaire. The most commonly reported symptoms were identified, and descriptions refined in 11 semi‐structured interviews. The questionnaire design was reviewed by a focus group. Content validity was established by a panel of expert health professionals. Seventy patients completed both the symptom questionnaire and a health‐related QoL questionnaire (EQ‐5D‐5L). Results: Thirteen common symptoms were identified. During the content validity phase, 13/16 experts responded (81%); 10/13 symptoms had 'excellent' or 'good' evaluation scores, and the content validity index of the whole questionnaire was 0.81, falling within the recommended threshold. Total symptom frequency scores, number of symptoms and the frequencies of 10/13 individual symptoms were all strongly associated with health‐related QoL (EQ‐5D‐5L index score; p < 0.002 for all). Conclusion: This work has provided a new, validated symptom score for patients with CKD not requiring RRT for clinical management and research purposes.